(untitled) (Kronika Bydgoska, 2018)
The purpose of the article is presentation of the libraries in Western Pomerania described by selected press reports in 1945-1950. The author analyzed 57 writings. Articles regarding libraries in those years were featured in such newspapers as “Kurier Szczeciński,” “Głos Szczeciński,” “Dziennik Bałtycki,” “Wiadomości Koszalińskie,” “Ilustrowany Kurier Polski,” “Przegląd Zachodni,” “Ziemia Pomorska,” and “Odra.” The research conducted indicates that press played an important role in the development process of public libraries in Western Pomerania, although information contained in it does not reflect reality.